Prevalence of Diabetes Mellitus and Its Risk Factors among Individuals Aged 15 Years and Above in Mizan-Aman Town, Southwest Ethiopia, 2016: A Cross Sectional Study - Shiferaw Birhanu Aynalem; Ayalew Jejaw Zeleke (International Journal of Endocrinology)
Introduction. Diabetes mellitus (DM), which is related to cardiovascular disease, is one of the main global health problems. In Ethiopia, information about this disease is known to be scarce. Objective. To assess the prevalence of diabetes mellitus and its risk factors among individuals aged 15 years and above. Methods. A community-based cross sectional study was carried out from January 01 to March 30, 2016 in Mizan-Aman town, southwest Ethiopia. A multistage sampling technique was used to select study participants. The World Health Organization (WHO) stepwise approach for noncommunicable disease surveillance was deployed to collect data. Total cholesterol and triglyceride level measurements were done using the HumaStar 80 chemistry analyzer. Glucose meter was used to check fasting venous blood glucose level. Descriptive and logistic regression analyses were used. Results. A total of 402 participants were included in the study. The prevalence of DM was found to be 6.5% (26 out of 402). Of which, the proportion of previously undiagnosed diabetes mellitus was 88.5%. The prevalence of prediabetes was also found to be 15.9%. The waist circumference (WC), body mass index, smoking habit, hypertension, and total cholesterol level were significantly associated with diabetes mellitus. Conclusion. In this study, higher prevalence of diabetes mellitus was observed than the IDFA-projected estimate of DM for Ethiopia. Modifiable associated risk factors were also identified. Therefore, targeting the prevention strategy to such modifiable risk factors might reduce the prevalence of diabetes mellitus and screening of DM particularly in those individuals having high WC, history of smoking habit, and hypertension needs attention.